Management ties and firm performance: Influence of family governance. Issue 2 (June 2019) - Lee, Tingko
Abstract: The relationship between managerial ties and firm performance has gained attention in the organization and management literature. However, existing studies that have examined the relationship between managerial ties and firm performance have reported inconsistent results. Drawing from agency theory, socioemotional wealth and the resource-based view, this study further examines the above relationship by investigating the probable influence of the family ownership role. Specifically, the present article investigates how family ownership moderates the influence of business and political ties on the return on assets (ROA) of public firms in Taiwan from 2013–2015. The findings show that business ties have a greater impact on the performance of family firms than nonfamily firms. However, the negative impact of political ties on firm performance is greater for family firms than nonfamily firms. Overall, the results provide an interesting implication: Although developing business ties is still a useful strategy for Taiwanese family firms, political ties are less important than in other countries. Therefore, business ties ensure the overall health and well-being of family firms that are more likely to contribute to the betterment of society.